Evaluation of Education in Islamic Education - Ela Fadila Azmi; Irfan Hidayat; Abdul Azhari (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
Islamic education has the primary goal of shaping a generation that is faithful, pious, and possesses noble character. This study aims to understand the educational evaluation system in Islamic education, focusing on the application of Islamic values and the effectiveness of teaching methods in Islamic educational institutions. This research employs a qualitative literature review method, analyzing various sources such as journal articles and books related to evaluation within the context of Islamic education. The findings show that proper and continuous evaluation in Islamic education plays a crucial role in improving the quality of teaching and learning. This evaluation also helps ensure that the Islamic values taught in schools align with the overall goals of Islamic education. With effective evaluation, educators can adjust their teaching methods and strategies to deliver the material to students better.